The Bronze Age Begins : The Ceramics Revolution of Early Minoan I and the New Forms of Wealth that Transformed Prehistoric Society - Betancourt, Philip P. (INSTAP Academic Press, 2009)
This book focuses on economic and social changes, particularly during the opening phase of the Minoan civilization on the island of Crete. New developments in ceramics that reached Crete at the end of the Neolithic period greatly contributed to the creation of economic, technological, social, and religious advancements we call the Early Bronze Age. The arguments are two-fold: a detailed explanation of the ceramics we call Early Minoan I and the differences that set it apart from its predecessors, and an explanation of how these new and highly superior containers changed the storage, transport